RETRACTED: Effect and Potential Mechanism of Lactobacillus plantarum Q7 on Hyperuricemia in vitro and in vivo - Cao, Jiayuan; Bu, Yushan; Hao, Haining; Liu, Qiqi; Wang, Ting; Liu, Yisuo; Yi, Huaxi (Frontiers in Nutrition, 2022)
Hyperuricemia (HUA) is a disorder of purine metabolism resulting in abnormally elevated serum uric acid (UA) concentration. It is believed there is an association between gut microbiota and HUA, and probiotics have the potential palliative effect. However, the underlying mechanism of probiotics in ameliorating HUA remains unclear. The purpose of this study was to investigate the effect and mechanism of Lactobacillus plantarum Q7 on HUA in Balb/c mice. The results showed that L. plantarum Q7 had excellent capability to affect UA metabolism, which could degrade nucleotides by 99.97%, nucleosides by 99.15%, purine by 87.35% and UA by 81.30%. It was observed that L. plantarum Q7 could down-regulate serum UA, blood urea nitrogen (BUN), creatinine (Cr) and xanthine oxidase (XOD) by 47.24%, 14.59%, 54.59% and 40.80%, respectively. Oral administration of L. plantarum Q7 could restore the liver, kidney and intestinal injury induced by HUA and the expression of metabolic enzymes and transporters to normal level. 16S rRNA sequencing analysis showed L. plantarum Q7 treatment could restore the imbalance of species diversity, richness and community evenness compared with the model group. The ratio of Bacteroidetes to Firmicutes was recovered nearly to the normal level by L. plantarum Q7 intervention. The dominant microorganisms of L. plantarum Q7 group contained more anti-inflammatory bacteria than those of model group. These findings indicated that L. plantarum Q7 might regulate UA metabolism and repair the liver, kidney injury by reshaping the gut microbiota and could be used as potential probiotic strain to ameliorate HUA.